Assessing the impact of integrated natural resources management: CIAT challenges and experiences - Gottret, María Verónica; White, D. (International Center for Tropical Agriculture, 2000)
Advances and travails of CIAT scientists as they develop and implement an impact assessment (IA) framework for three integrated natural resources management (INRM) sites in Latin America (hillsides, savannas and forest margins) is presented. Also, the importance and growing interest of IA for INRM research as a planning , learning and accountability tool is underlined. The document present a brief historical perspective of the relationship between development thought and IA methodologies, and analyses the major challenges of developing and implementing and appropriate methodology that satisfies the needs of multiple stake holders. A conceptual and analytical framework for INRM research IA, along with first insights about CIAT efforts on implementing an IA process in its INRM sites is proposed. The proposed IA methodology would permit tracking relevant types of changes over time. However, establishing cause-effect or at least influence linkages, is more complex and is not as simple. Therefore, there is a need for further IA research to develop a model for assessing and validating the path-to-development impact in order to evaluate the contribution or at least the influence, of a given intervention to final development goals. This model could also be useful to conduct ex-ante impact analysis of different research and development interventions from organizational models to decision-support tools to technology and information as a criteria for INRM research priority-setting.